2005
DOI: 10.1016/j.jasms.2005.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional protein identification technology (MudPIT): Technical overview of a profiling method optimized for the comprehensive proteomic investigation of normal and diseased heart tissue

Abstract: An optimized analytical expression profiling strategy based on gel-free multidimensional protein identification technology (MudPIT) is reported for the systematic investigation of biochemical (mal)-adaptations associated with healthy and diseased heart tissue. Enhanced shotgun proteomic detection coverage and improved biological inference is achieved by pre-fractionation of excised mouse cardiac muscle into subcellular components, with each organellar fraction investigated exhaustively using multiple repeat Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(102 citation statements)
references
References 39 publications
2
100
0
Order By: Relevance
“…Next, we tested several fractionation protocols based on differential centrifugation at different sucrose densities [8,13]. In our hands, these laborious protocols gave variable degrees of B23 and total protein recovery in the nuclear fraction (data not shown).…”
Section: Nuclear Protein Extraction Proceduresmentioning
confidence: 97%
“…Next, we tested several fractionation protocols based on differential centrifugation at different sucrose densities [8,13]. In our hands, these laborious protocols gave variable degrees of B23 and total protein recovery in the nuclear fraction (data not shown).…”
Section: Nuclear Protein Extraction Proceduresmentioning
confidence: 97%
“…Though, greater sensitivity leads to much higher variability in peptide detection at each fractionation step from run to run, demanding a greater number of technical replicas, which compromises the overall throughput. Several groups have evaluated the number of replicates necessary to observe a particular percentage of the proteins in a sample (Liu et al, 2004;Slebos et al, 2008;Kislinger et al, 2005). On the other hand, Tabb et al (2009) concluded that a standardized platforms results a high degree of repeatability and reproducibility (around 70-80%) in protein identifications.…”
Section: Lc-ms Repeatability and Reproducibilitymentioning
confidence: 99%
“…Sethuraman et al [118] simultaneously identified and quantified oxidant-sensitive cysteine thiols from a rabbit heart membrane fraction treated with H 2 O 2 using isotope-coded affinity tag (ICAT) reagent [119], which specifically labels the thiol groups of free cysteine. Furthermore, dedicated MS-based methods have been developed to study oxidations at other specific residues (reviewed in [120]), and advancements in the fields of MudPIT [121] and "top-down" MS [122] greatly enhanced the ability to thoroughly interrogate protein modifications.…”
Section: Oxidation and Nitrosylationmentioning
confidence: 99%